Patogenicidad de Phylloporia chrysita (Aphyllophorales: Hymenochaetaceae) sobre Erythrochiton gymnanthus (Rutaceae) - Esquivel, Rhina E. (1996)
The pathogenicity of Phylloporia chrysita (Berk.) Ryv. on Erythrochiton gymnanthus K. (Rutaceae) was studied in Carara Hological Reserve, seasonal Pacific of Costa Rica. Growth rate and distribution of basidiocarps were determined on healthy and diseased plants. P. chrysita caused 52% growth reduction on diseased plants. Fungal hyphae were observed on epidermis, parenchyma and vascular issue, where they caused cellular breakdown.